On Life-Narrative - Sharifah Sophia, Wan Ahmad (Universiti Malaysia Sarawak, (UNIMAS), 2013)
This essay takes issue with the assumption of autonomy current to the thinking on autobiography. It explores the approaches at looking into autobiography and asks how these approaches perpetuated the myth of an autonomous author. As an alternative, a sociological approach is presented as it undermines this liberal fiction. Although the paper does not provide an answer related to autonomy, it hopes that it can at least raise a question about the epistemological problem associated with libertarian concepts such as freedom and agency